The Relationship between Sport and Stress in Medical Faculty Student Students Malang Muhammadiyah University - Iwan Sis Indrawanto; Muthia Putrinahrisyah; Hanna Cakrawati (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Medical students are prone to experiencing stress during the lecture period due to the demands of the learning process. Women experience stress more easily than men due to a higher body response to stress. Exercise is known to help reduce stress because it stimulates the release of endorphins in the body. The purpose of this study was to determine whether there is a relationship between sports activity and stress in female students at the Faculty of Medicine, University of Muhammadiyah Malang. The research was conducted in January 2021 with a sample of 127 people and was taken using the technique of purposive sampling, that is, female students who are sampled must comply with the inclusion and exclusion criteria. Data was collected using a questionnaire (Godin-Shepard). Leisure Time Physical Activity and Depression, Anxiety, and Stress Scale (THAT)-21 The results of data analysis using the Kruskal-Wallis test show a value of p = 0.614 (p > 0.05), which indicates that there is no relationship between sports activity and stress levels in female students at the Faculty of Medicine, University of Muhammadiyah Malang